Variability of southwest monsoon over Rajasthan and Kerala (MAUSAM, 2005)
The onset, withdrawal dates and rainfall of southwest monsoon corresponding to east and west Rajasthan sub-divisions have been examined statistically for the past 63 years (1941-2003) to bring out some major aspects of their variability and trend to predict these parameters of southwest monsoon over Rajasthan. Various correlation coefficients have been worked out. Study reveals, shift in monsoon activity, enhancement of monsoon duration, early onset and late withdrawal enhances monsoon duration and seasonal rainfall over Rajasthan. Early onset over east Rajasthan certainly brings early onset over west Rajasthan.